Distribution of Hydrogenases in Cyanobacteria: A Phylum-Wide Genomic Survey - Puggioni, Vincenzo; Tempel, Sébastien; Latifi, Amel (Frontiers in Genetics, 2016)
Microbial Molecular hydrogen (H2) cycling plays an important role in several ecological niches. Hydrogenases (H2ases), enzymes involved in H2 metabolism, are of great interest for investigating microbial communities and producing BioH2. To obtain an overall picture of the genetic ability of Cyanobacteria to produce H2ases, we conducted a phylum wide analysis of the distribution of the genes encoding these enzymes in 130 cyanobacterial genomes. The concomitant presence of the H2ase and genes involved in the maturation process, and that of well-conserved catalytic sites in the enzymes were the three minimal criteria used to classify a strain as being able to produce a functional H2ase. The [NiFe] H2ases were found to be the only enzymes present in this phylum. Fifty-five strains were found to be potentially able produce the bidirectional Hox enzyme and thirty three to produce the uptake (Hup) enzyme. H2 metabolism in Cyanobacteria has a broad ecological distribution, since only the genomes of strains collected from the open ocean do not possess hox genes. In addition, the presence of H2ase was found to increase in the late branching clades of the phylogenetic tree of the species. Surprisingly, five cyanobacterial genomes were found to possess homologues of oxygen tolerant H2ases belonging to groups 1, 3b and 3d. Overall, these data show that H2ases are widely distributed, and are therefore probably of great functional importance in Cyanobacteria. The present finding that homologues to oxygen-tolerant H2ases are present in this phylum opens new perspectives for applying the process of photosynthesis in the field of H2 production.